Pengembangan Usaha UKMBandeng Duri Lunak di Kelurahan Krobokan Kota Semarang - Arliawan, Surya; Suryoko, Sri (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2016)
Small Business Enterprise’s has grown to be an important element in the development of various countries in the world because it absorbs the largest labor and as a contribution to the gross great domestic income. Krobokan is one village in the district of west side of Semarang. It is one of the industrial centers mainly milkfish soft spines. Fish isconsiderable potentialindustrial materialsconsidering that Indonesiaisa maritime country, mostly in the form ofoceanterritory. Based on thefactsaboutthe potential offish commodities, most residents ofthe Village Krobokan pursue small milk fish industry. The purpose of this study is to analyze how the development of SME’s milkfish soft spins in running the business seen from the capital, human resources, technology, and marketing use. This study uses a qualitative, descriptive. The research located in the Village of Krobokan Semarang who have eight (8) SME’s Milkfish Softspins by interview, observation, and the collection of related documents. The data were analyzed qualitatively by using the step data reduction, data presentation, and conclusion.The results showed that the milkfish soft spines bussines in Kerobokan have occupied at least 10 years and some even more than 20 years. Of the business more than 10 years; from the aspect of capital increased 5 – 10 times significantly. Business assets to increase both quality and quantity. From the aspect of human resources in general there is no increase in the manpower; but the skills of how to increase the quality of processing. From the technological aspects of the majority (62.5%) experienced an increase in both the quality and quantity of tools and packaging aspects. From the aspect of marketing in general there is an increase in sales volume; but only a small proportion (37.5%) who had more than one market services.